Profitability Ratio Analysis To Assess Financial Performance At PT Akasha Wira International Tbk - Nely Puspita Sari; Neri Susanti; Yun Fitriano (Penerbit Jurnal Indonesia, 2023)
One of the tools for assessing financial performance is the profitability ratio analysis, which aims to measure overall management effectiveness indicated by the level of profit obtained, whether large or small. The better the profitability ratio, the better a company's ability to generate profits.,The purpose of this research is to assess the financial performance of PT Akasha Wira International Tbk for the period 2018-2022. Data collection methods include documentation and literature study, and the analysis method used is descriptive analysis with a quantitative approach, using profitability ratio analysis, including Gross Profit Margin, Net Profit Margin, Return On Investment, and Return On Equity. The research results indicate that both Gross Profit Margin and Net Profit Margin increased continuously from 2018 to 2022, with an average of over 15%, indicating excellent performance. Return On Investment showed an increase from 2018 to 2021 and a slight decrease in 2022 but still falls within the good category with an average of 14.59%. Return On Equity increased from 2018 to 2021, with a slight decrease in 2022 compared to the previous year but still maintains an excellent average of 19.98%.